The fiscal and monetary institutions of CESEE countries - Zsolt Darvas; Valentina Kostyleva (Bruegel, 2011)
This paper examines the role of fiscal and monetary institutions in macroeconomic stability and budgetary control in CESEE (central, eastern and south eastern European) countries in comparison to other OECD countries. CESEE countries tend to grow faster (at least before the crisis) and have more volatile output than non-CESEE OECD countries, which has implications for macroeconomic management: better fiscal and monetary institutions are needed to avoid pro-cyclical policies. Our budgetary discipline index suggests that fiscal institutions are weaker in most CESEE countries than in non-CESEE OECD countries. The pre-crisis declines in CESEE debt/GDP ratios were largely the consequence of a very favourable relationship between the economic growth rate and the interest rate, but such a favourable relationship cannot be expected to continue. Our econometric estimations confirm that better monetary institutions reduce macroeconomic volatility, and countries with better budgetary procedures had better fiscal outcomes. All these factors call for improved monetary institutions, stronger fiscal rules, and better budgetary procedures.
Keywords: 330; Finanzpolitik; Haushaltsplanung; Geldpolitik; Institutionelle Infrastruktur; Makroökonomischer Einfluss; EU-Staaten (Osteuropa); Südosteuropa